Performance of Pyridylthiourea‐Polyethylenimine Polyplex for siRNA‐Mediated Liver Cancer Therapy in Cell Monolayer, Spheroid, and Tumor Xenograft Models - Jean Baptiste Gossart; Etienne Pascal; Florent Meyer; Emilie Heuillard; Mathieu Gonçalves; Francine Gossé; Eric Robinet; Benoît Frisch; Cendrine Seguin; Guy Zuber (Global Challenges, 2017)
Medical application of siRNAs relies on methods for delivering nucleic acids into the cytosol. Synthetic carriers, which assemble with nucleic acids into delivery systems, show promises for cancer therapy but efficiency remains to be improved. In here, the effectiveness of pyridylthiourea‐polyethylenimine (πPEI), a siRNA carrier that favors both polyplex disassembly and endosome rupture upon sensing the acidic endosomal environment, in 3 experimental models of hepatocellular cancer is tested. The πPEI‐assisted delivery of a siRNA targeting the polo‐like kinase 1 into Huh‐7 monolayer produces a 90% cell death via a demonstrated RNA interference mechanism. Incubation of polyplex with Huh‐7 spheroids leads to siRNA delivery into the superficial first cell layer and a 60% reduction in spheroid growth compared to untreated controls. Administration of polyplexes into mice bearing subcutaneous implanted Huh‐7Luc tumors results in a reduced tumor progression, similar to the one observed in the spheroid model. Altogether, these results support the in vivo use of synthetic and dedicated polymers for increasing siRNA‐mediated gene knockdown, and their clinical promise in cancer therapeutics.